Legal Resolution of the Land Dispute over Former Recht Van Eigendom of Taman Sriwedari Surakarta and the Solo City Government - Utomo, Chelsy Naristya; Ramli, Asmarani; Suhadi, Suhadi (Indonesian Journal of Agrarian Law, 2026)
Sriwedari Park in Surakarta is a cultural heritage area that has high historical and social value, but has experienced a prolonged land dispute since 1970. This study aims to analyze the settlement of the land dispute of the former Recht van Eigendom (RvE) Verponding No. 259 between the heirs of KRMT Wirjodiningrat and the Solo City Government. The object of the research is the process of converting colonial land rights into national rights based on the Basic Agrarian Law (UUPA), as well as the legal and policy dynamics surrounding the dispute. The research method used is an empirical juridical approach. The results of the study show that although the process of conversion of rights has been in accordance with the law through the issuance of Building Rights (HGB) No. 22 in 1965, the Solo City Government continues to control the land factually and issue the right of use unilaterally, even though it has been defeated in a series of court decisions to the level of review. Non-compliance with court rulings reflects weak law enforcement and the dominance of local political interests over citizens' property rights. This study concludes that dispute resolution requires political commitment from local governments, intervention from supervisory institutions, and administrative and juridical restitution of rights to heirs.